Pengaruh Perilaku Konsumen Dan Store Atmosphere Terhadap Keputusan Pembelian Pada Cafe The Scoop Di Kabupaten Kolaka - Andry Stepahnie Titing; Ismanto Ismanto; Tenri Wahyuni (Transformasi: Journal of Economics and Business Management, 2023)
The purpose of this study is to determine: (1) the impact of consumer behavior on purchase decisions at The Scoop café in Kolaka district, and (2) the impact of store atmosphere on purchasing decisions in Kolaka district. This is a quantitative study with an explanatory research model that use a questionnaire as an instrument. In this study, the population consisted of all consumers who had purchased The Scoop café products, with a total sample of 70 respondents recruited by observation, documentation, and questionnaire procedures. There are two types of data collection techniques: primary data and secondary data. SPSS 25 was used to examine the study instrument's validity and reliability. The Structural Equation Modeling (SEM-PLS) method using SmartPLS 3.0 was utilized to analyze the research data. The results show that Consumer Behavior has a favorable and significant impact on Consumer Purchase Decisions. This is demonstrated by the t-count or t-statistic of 2.816, which is more than the t-table value of > 1.66. P-values of 0.003. Meanwhile, because the t-count or t-statistic value is 7.619, which is greater than the t-table value > 1.66 with a P-value of 0.000, Store Atmosphere has a positive and substantial effect on Consumer Purchase Decisions. Consumer Behavior and Store Atmosphere then have a 92.7% favorable and substantial effect on Consumer Purchase Decisions